Analyzing the students’ motivation to learn English - aam alamsyah (Journal of Informatics and Communication Technology (JICT), 2020)
Identifying motivational factors in every field is always important. Likewise, identifying the student’s motivation to learn English is important so that the teachers or the other relevant education stakeholders can take more specific action regarding their students’ motivation. Especially, since motivation is a driving force affecting human’s life, the attempt to analyze the factors affecting the students’ motivation is always important. The present study was conducted in a private telecommunication college. The research method employed was a survey research with additional limited interview. The number of the participants recruited for the study was 40 students. The students recruited were the active students who are currently studying in their fourth/fifth semester. Of the whole factors questioned to the students, the lecturers were found to be the most significant factors affecting the students’ motivation. The other factors affecting the students’ motivation were the teaching media, such as internet and library. The finding also confirms the previous studies suggesting the important role of teachers/lecturers in serving the students. The students also indicated that the role of lecturers in facilitating their learning process, which was getting more complicated during the pandemic, as the most important factor leading to better motivation. Lastly, in terms of relationship, parents were found to be important as they could possibly support the students’ spirit to learn English regardless of their learning context. Keywords: Analyzing, the students’ motivation, learn, English